Cerebral Microbleeds in Fragile X–Associated Tremor/Ataxia Syndrome. Issue 8 (24th March 2021) - Salcedo‐Arellano, María Jimena; Wang, Jun Yi; McLennan, Yingratana A.; Doan, Mai; Cabal‐Herrera, Ana Maria; Jimenez, Sara; Wolf‐Ochoa, Marisol W.; Sanchez, Desiree; Juarez, Pablo; Tassone, Flora; Durbin‐Johnson, Blythe; Hagerman, Randi J.; et al.
Abstract: Background: Fragile X–associated tremor/ataxia syndrome is a neurodegenerative disease of late onset developed by carriers of the premutation in the fragile x mental retardation 1 ( FMR1 ) gene. Pathological features of neurodegeneration in fragile X–associated tremor/ataxia syndrome include toxic levels of FMR1 mRNA, ubiquitin‐positive intranuclear inclusions, white matter disease, iron accumulation, and a proinflammatory state. Objective: The objective of this study was to analyze the presence of cerebral microbleeds in the brains of patients with fragile X–associated tremor/ataxia syndrome and investigate plausible causes for cerebral microbleeds in fragile X–associated tremor/ataxia syndrome. Methods: We collected cerebral and cerebellar tissue from 15 fragile X–associated tremor/ataxia syndrome cases and 15 control cases carrying FMR1 normal alleles. We performed hematoxylin and eosin, Perls and Congo red stains, ubiquitin, and amyloid β protein immunostaining. We quantified the number of cerebral microbleeds, amount of iron, presence of amyloid β within the capillaries, and number of endothelial cells containing intranuclear inclusions. We evaluated the relationships between pathological findings using correlation analysis. Results: We found intranuclear inclusions in the endothelial cells of capillaries and an increased number of cerebral microbleeds in the brains of those with fragile X–associated tremor/ataxia syndrome, both of which are indicators of cerebrovascular dysfunction. We also found a suggestive association between the amount of capillaries that contain amyloid β in the cerebral cortex and the rate of disease progression. Conclusion: We propose microangiopathy as a pathologic feature of fragile X–associated tremor/ataxia syndrome. © 2021 International Parkinson and Movement Disorder Society